Webpages on copyright in Canadian academic libraries - Horava, Tony (Université d'Ottawa | University of Ottawa, 2008)
Academic libraries value the web as being a vital channel for communicating information and policies to their user community. Designing a webpage on copyright is a challenging task that requires a onsideration of the medium and the message. This article proposes a onceptual model and proactive approach for integrating policy objectives and goals into the development of a copyright webpage, based on key elements of the library's mission in the academic environment. To complement this theoretical approach, an analysis of Canadian academic library websites was conducted in order to gage the effectiveness of copyright webpages, in the Canadian legal context, as well as related design issues of visibility and access.
Keywords: Copyright; academic libraries; Canada; Web; policies; education